DAMPAK KEBUDAYAAN ASING TERHADAP KEBUDAYAAN LOKAL DALAM KEHIDUPAN MASYARAKAT - Mauizatul Hasanah; Halija Halija (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2023)
This paper will explain the influence of foreign culture and local culture on society. Culture is the whole system of ideas, actions, and the results of human work in the context of community life that humans have by learning. In social life, of course, there is a foreign cultural influence on local culture that enters the community. In the era of globalization, the influence of foreign cultures can have positive and negative impacts. Positive impact, namely, millions of people / youth, one person against another, one ethnic group against another ethnic group, one nation against another nation. And the negative impact, namely, from the development of the era which is increasingly intensifying life, in addition to technology being more in front and making it easier to dig up information, causing our country to be penetrated by culture by developed countries. Efforts to overcome the negative impact of foreign culture, how to anticipate the bad impact of foreign culture into local culture in Indonesia, especially anticipating the younger generation, to prevent this bad impact it is necessary to have the participation of various groups, most importantly support from the government and from the environment around us, for example ustad, besides a who have broad insight into the culture and most importantly their parents. With the entry of foreign cultural influences into people's lives, it will have a lot of impacts, both bad impacts and good impacts. Therefore, the public and the government must be more careful in selecting the incoming foreign cultural influences, do not take it for granted without selecting it first.